Freud's Memory - White, R. author. aut Link
VI, 183 p.
Keywords: Rob White reconsiders Freud's controversial theory of inherited memory, referring it both to Anglo-American commentary and post-structuralist work on psychoanalysis. White proposes that this theory is evidence of an underlying haunted retrospection in Freudian theorizing, which time and again discovers that meaning has been lost.